The importance of beachgoers as a source of beach litter - Nwaigwe, Chukwudi (Department of Biological Sciences, 2026)
The increasing prevalence of anthropogenic litter on beaches is a significant environmental concern. Various waste materials, including plastics, wood, metal, and paper, often enter coastal environments through direct disposal or indirect pathways such as rivers, storm drains, and beach and ocean users. This pollution poses serious threats to the aesthetic and recreational value of beaches, local economies, and the well-being of beachgoers. Additionally, it has detrimental impacts on terrestrial and marine ecosystems. Reducing litter on beaches requires an understanding of key pollution sources to implement effective mitigation actions and strategies. Beach litter could originate from various sources, including beachgoers. When attributing sources to beach litter, various approaches have been applied but all have shortcomings. This study evaluates the dry and wet sand methodology, which was devised by Barnardo and Ribbink (2020) and Ryan et al. (2020b) and has since been used by Barnardo et al. (2021) and Okuku et al. (2020) to identify beach litter originating from beachgoers, although it has not been validated. I compared litter accumulation at two urban beaches in False Bay, South Africa: Muizenberg, a popular recreational beach, and Sunrise Beach, a nearby, less utilised beach. Data from April 2023, when beaches were open to visitors, were compared to April 2020, when beaches were closed during the COVID-19 pandemic. Findings examined whether the dry sand component reflected differences between years with and without visitors, providing insight into the method's effectiveness. I recorded greater litter loads at Muizenberg than at Sunrise Beach during both sampling years. Between sampling years, more litter was collected during 2020 than 2023 at both beaches. More onshore winds in 2020 likely contributed to litter deposition, while in 2023, when visitors were present, informal beach cleaning would have contributed to the presence of less litter. Litter composition varied by sampling years and beaches. At Muizenberg in 2023, dry sand items were dominated by smoking-related items (mainly cigarette butts) and items made from paper. At Sunrise, single use plastics (such as food and packaging items) dominated in both sampling years. In 2023, dry sand litter accounted for 23% of items and 43% of litter mass at Muizenberg, compared to 6% and 12% at Sunrise, respectively. The amount and composition of the dry sand litter at Muizenberg suggests a correlation with the number of beachgoers the day before, which indicates the potential to use the dry and wet sand method as a proxy for litter generated by beachgoers. I applied the dry and wet sand daily accumulation method to infer the relative contribution of beachgoers to litter loads seasonally at both beaches. The proportion of dry sand litter was higher in summer (when the number of beachgoers was greater) at both beaches compared to other seasons, especially at Muizenberg. Items made from paper and smoking-related items (mainly cigarette butts) dominated by number and mass on the dry sand, especially in summer. On the wet sand, smoking-related items predominated by number and large non-plastic items (such as a car tyre, processed wood, etc.) by mass, mainly in the winter rainy season. These findings suggest that more effective mitigation measures are needed, particularly during summer. These could include increased educational awareness campaigns, the installation of additional waste bins, and increased beach clean-up efforts. I also investigated whether beachgoer litter is a major source of litter in the surf zone. I compared the composition of litter in the surf zone to that on the sandy beach over 50-days in 2022/23, repeating a previous study performed in 2013/14. Daily net tows in the surf zone revealed that litter abundance had decreased since 2013/14. A negative correlation between surf zone litter and the number of beachgoers the previous day suggests that little of the surf zone litter derives directly from beachgoer activity. It is more likely that weather conditions influence both the amount of surf zone litter and beach attendance. Most litter sampled in the surf zone was smaller than that collected on beaches because the 5 mm-mesh net used to sample in the surf zone collected smaller items than items collected by hand on the beach > 10 mm. During offshore winds, small amounts of litter typically found on the dry sand were collected from the surf zone on a few of the sampling days. Findings suggest that only a small fraction of beach litter migrates offshore via the surf zone. In addition, 35% of the litter collected in the surf zone in 2022/23 and 18% in 2013/14 showed signs of weathering, indicating a prolonged time in the sea. In summary, this study validates the use of the dry and wet sand daily accumulation methodology for assessing beach litter contributions from beach users. It also highlights seasonal variations in litter accumulation, particularly on urban beaches. Dry sand litter was most prevalent in summer, linked to an increase in the number of visitors and their tendency to leave waste behind However, there was no strong evidence linking beachgoer litter to the amount in the adjacent surf zone. While findings suggest that only a small proportion of sandy beach litter generated by beachgoers migrates into the nearby sea, interventions to manage beach littering, such as more waste bins, public awareness campaigns, and stricter enforcement policies would be beneficial.